THE DIPLOMACY OF BOURGEOIS PACIFISM IN THE INTERNATIONAL ACTIVITIES OF WESTERN EUROPEAN COUNTRIES AT THE EARLY 1920-S - Священко, Зінаїда (SWorldJournal, 2024)
The article is devoted to the international relations of the countries of Western Europe in the 1920s, which entered the history of world diplomacy as the "era of bourgeois pacifism". The pacifist programs of France and Great Britain are considered, amon